Elevated Glucose Levels Favor SARS-CoV-2 Infection and Monocyte Response through a HIF-1α/Glycolysis-Dependent Axis - Codo, Ana Campos; Davanzo, Gustavo Gastão; Monteiro, Lauar de Brito; de Souza, Gabriela Fabiano; Muraro, Stéfanie Primon; Virgilio-da-Silva, João Victor; Prodonoff, Juliana Silveira; Carregari, Victor Corasolla; de Biagi Junior, Carlos Alberto Oliveira; Crunfli, Fernanda; Jimenez Restrepo, Jeffersson Leandro; Vendramini, Pedro Henrique; et al. (Elsevier, 2020)
COVID-19 can result in severe lung injury. It remained to be determined why diabetic individuals with uncontrolled glucose levels are more prone to develop the severe form of COVID-19. The molecular mechanism underlying SARS-CoV-2 infection and what determines the onset of the cytokine storm found in severe COVID-19 patients are unknown. Monocytes and macrophages are the most enriched immune cell types in the lungs of COVID-19 patients and appear to have a central role in the pathogenicity of the disease. These cells adapt their metabolism upon infection and become highly glycolytic, which facilitates SARS-CoV-2 replication. The infection triggers mitochondrial ROS production, which induces stabilization of hypoxia-inducible factor-1α (HIF-1α) and consequently promotes glycolysis. HIF-1α-induced changes in monocyte metabolism by SARS-CoV-2 infection directly inhibit T cell response and reduce epithelial cell survival. Targeting HIF-1ɑ may have great therapeutic potential for the development of novel drugs to treat COVID-19. Diabetic people with uncontrolled blood glucose levels have a greater risk to develop severe COVID-19 disease. Codo et al. show that elevated glucose levels and glycolysis promote SARS-CoV-2 (CoV-2) replication and cytokine production in monocytes through a mitochondrial ROS/hypoxia-inducible factor-1α dependent pathway, resulting in T cell dysfunction and epithelial cell death.
Keywords: Covid-19; diabetes; glycolysis; HIF-1alpha; inflammation; interferon; metabolism; mitochondria; monocyte; SARS-CoV-2